Mineral and crude protein content of natural pastures on Adamawa highlands, Cameroon - Moffor, F.M.N.; Yonkeu, S.; Tawah, C.L.; Mbah, D.A.; Pano, E.T. (1994)
Mineral and crude protein content of natural pastures of the Adamawa Highlands of Cameroon were studied over a 12-month period. Samples of predominantly grazed graminae of these pastures were collected from basaltic and granitic soil types and analyzed for calcium (Ca), phosphorus (P) magnesium (Mg), potassium (K) and crude protein (CP) levels. Mineral and crude protein levels varied significantly with soil type, season and protein of plant sampled. Calcium, P, Mg, K and CP concentrations averaged 0.24 0.10, 0.20, 0.777 and 3.20 percent respectively indicating deficiencies in Ca, P an CBasaltic soil pastures had higher levels of Ca, P, Mg and CP than those of granitic soils. Calcium and Mg levels were significantly lower in pastures during the wet season than in the dry season. Potassium and CP levels were significantly lower in the pastures during the dry seasons necessitating phosphorus supplementation year round. Use of adapted legume forages and fertilization of natural pastures were suggested as alternatives to supplementation.